2010
DOI: 10.1097/prs.0b013e3181d6e7b8
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithmic Approach to Breast Reconstruction Using Latissimus Dorsi Myocutaneous Flaps

Abstract: The authors have developed an algorithmic approach to latissimus dorsi myocutaneous flap breast reconstruction. Through critical evaluation of mastectomy defects, reconstructive breast surgeons can tailor skin island orientation, minimize donor-site scarring, enhance cosmetic outcomes, and provide a durable and natural aesthetic outcome in breast reconstruction with the latissimus dorsi myocutaneous flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Minimizing direct contact between the prosthesis and the overlying irradiated tissue using an autologous flap may ultimately increase the rate of successful reconstructions. 42 There are several important limitations to this study which merit discussion. First, there was the potential for a significant degree of heterogeneity in patient populations, studies, and reconstructions.…”
Section: Discussionmentioning
confidence: 97%
“…Minimizing direct contact between the prosthesis and the overlying irradiated tissue using an autologous flap may ultimately increase the rate of successful reconstructions. 42 There are several important limitations to this study which merit discussion. First, there was the potential for a significant degree of heterogeneity in patient populations, studies, and reconstructions.…”
Section: Discussionmentioning
confidence: 97%
“…4,18 Although one must consider the donor-site seroma in cases of reconstruction, all noted in this study were amenable to treatment in the outpatient clinic. Various authors have suggested the use of more extensive quilting sutures, steroids, and/or fibrin glues to further reduce the incidence.…”
Section: Discussionmentioning
confidence: 97%
“…2 Some authors would only reserve implant-based latissimus dorsi breast reconstruction for patients who do not qualify for pure reconstructive techniques. 3,4 Although the use of the latissimus dorsi flap is gaining resurgence, 1,5-7 one must always consider the risk of capsular contracture, both in irradiated and in nonirradiated breasts. 8 -13 Previous published series of latissimus dorsi reconstructions have shown a capsular contracture rate affecting between 0 and 56 percent of patients 1,3,11,14 -21 (Table 1).…”
mentioning
confidence: 99%
“…T he latissimus dorsi (LD) musculocutaneous flap is commonly used for delayed breast reconstruction (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Herein, the authors present a change in technique from the traditional methods of LD musculocutaneous flap recipient site preparation, flap inset and breast shaping, to better address the requirements for an aesthetically pleasing breast in delayed breast reconstruction.…”
mentioning
confidence: 99%